Spotlight on the Effect of Workplace Ostracism on Creativity: A Social Cognitive Perspective - Tu, Ming; Cheng, Zhihui; Liu, Wenxing (Frontiers in Psychology, 2019)
Using a sample of 195 employees and their supervisors from one single Chinese company, the following conclusions were drawn: (1) workplace ostracism was negatively correlated to employee creativity, (2) employees’ creative self-efficacy mediated the relationship between workplace ostracism and employee creativity, and (3) employees’ collectivism (a value) moderated the relationship between workplace ostracism and employee creativity. Implications of these results for research and practice are discussed within.